Physico-chemical properties, bioactive compounds and color parameters of coriander puree: effect of pretreatments and freezing - Kaur, Gurjeet (J Food Sci Technol, 2018)
Coriander, one of the most widely utilized herb, is a short duration herb having very short shelf life. The present investigation involved development of an innovative process for enhancing the utilization and the availability of this herb. This process involves pretreatment, blanching and freezing to form ready to use frozen coriander puree tablets. Coriander was subjected to different pretreatments viz. T1: 0.25% potassium metabisulphite, T2: 0.5% citric acid and T3: 0.2% potassium metabisulphite + 0.1% magnesium chloride + 0.1% sodium bicarbonate. The pretreated coriander was blanched in hot water for 2 min and processed into puree having total soluble solids (TSS) as 2.5, 3.5 and 4.5°Brix. Pretreatments significantly affected the all quality parameters except moisture content. TSS had non significant effect on a* value, chroma, pH ascorbic acid and total flavonoid content of processed coriander puree. Coriander puree obtained with T1 pretreatment exhibited better quality than with other pretreatments. T1 pretreated and blanched puree was then frozen in silicon moulds using air blast freezing and deep freezing. Frozen puree tablets were evaluated for quality. The best quality coriander puree obtained from T1 pretreated, blanched puree having TSS 4.5°Brix frozen by continuous air-blast freezing (at a conveyor speed of 4.40 × 10(−3)m/s) comparable results to deep freezing having. All quality parameters, except pH, were significantly affected by TSS level of puree as well as different freezing treatments.